The importance of physiotherapy in gestational phases (Research, Society and Development, 2022)
The gestational process arises from fertilization and lasts for nine months, which can be divided into three trimesters, generating in each of them the modification of the woman's organism in a natural way. Therefore, expectations and doubts can be formed about how to know how to deal with these changes, considering that they can generate adaptation difficulties, taking into account physiological, psychological and physical changes. Therefore, the present work aims to evaluate the importance of the physiotherapy team throughout the gestational process, emphasizing its role in general among the multidisciplinary team that performs prenatal care and the follow-up of pregnant women from conception to delivery. The methodology used was performed through research based on an integrative review of the literature, with the purpose of allowing the complete analysis of studies and scientific articles in a systematic and broad way, where the literature review was prioritized. According to the findings, due to the consolidation of the work, it is concluded that it is of paramount importance of  physiotherapist's performance throughout the gestational process and in the puerperium, considering that it provides the well-being of the pregnant woman, prevents algias, discomfort and diseases or complications.